2021
DOI: 10.1016/j.ajog.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 in pregnancy was associated with maternal morbidity and preterm birth

Abstract: K.F.H. reports being an investigator on grants to Brigham and Women's Hospital from Eli Lilly and Company and GlaxoSmithKline for unrelated studies. B.T.B. reports being an investigator on grants to Brigham and Women's Hospital from Eli Lilly and Company, Baxalta, GlaxoSmithKline, and Pacira Pharmaceutical Inc for unrelated studies; received personal fees from Aetion Inc and from the Alosa Foundation outside the submitted work; and served on an expert panel for a postpartum hemorrhage quality improvement proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Based on populationbased cohort studies and systematic reviews, COVID-19 during pregnancy is associated with increased risks of adverse birth outcomes including preterm births and cesarean section deliveries without significant increase in the risk for low birth weight, asphyxia and other neonatal morbidity (13)(14)(15). Interestingly, Al-Lami et al suggested the biological evidence that SARS-CoV-2 might cause preterm labor in pregnant women with no medical indication for preterm labor induction and be related to the hypertensive disorders of pregnancy (16). While there is little evidence on the maternal-fetal vertical transmission of SARS-CoV-2, the neonatal SARS-CoV-2 infection is usually mild (15,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Based on populationbased cohort studies and systematic reviews, COVID-19 during pregnancy is associated with increased risks of adverse birth outcomes including preterm births and cesarean section deliveries without significant increase in the risk for low birth weight, asphyxia and other neonatal morbidity (13)(14)(15). Interestingly, Al-Lami et al suggested the biological evidence that SARS-CoV-2 might cause preterm labor in pregnant women with no medical indication for preterm labor induction and be related to the hypertensive disorders of pregnancy (16). While there is little evidence on the maternal-fetal vertical transmission of SARS-CoV-2, the neonatal SARS-CoV-2 infection is usually mild (15,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection is characterized by SARS-CoV-2 virus-induced widespread inflammation and cytokines storm that might involve many organs [41,42]. Specifically, COVID-19 in pregnancy is associated with adverse obstetrical outcomes with reports of high rates of preterm labor and preeclampsia or preeclampsia like syndrome, possibly through immune-altering effects [43][44][45][46][47][48][49][50][51][52]. There is a rising evidence of a causal relationship between COVID-19 infection during pregnancy and initiation of preterm labor [43,45,50].…”
Section: The Possible Implications Of 17-ohpc Immune Effects In Pregn...mentioning
confidence: 99%
“…Specifically, COVID-19 in pregnancy is associated with adverse obstetrical outcomes with reports of high rates of preterm labor and preeclampsia or preeclampsia like syndrome, possibly through immune-altering effects [43][44][45][46][47][48][49][50][51][52]. There is a rising evidence of a causal relationship between COVID-19 infection during pregnancy and initiation of preterm labor [43,45,50]. Although most of pregnant women with COVID-19 infection, especially severe cases, are being medically induced to deliver in order to improve their respiratory functions, there is biological evidence that SARS-CoV-2 virus could cause uterine contractions by using uterine ACE-2 receptor to induce the production of vasoconstricting inflammatory agents in the setting of SARS-CoV-2 viremia [45].…”
Section: The Possible Implications Of 17-ohpc Immune Effects In Pregn...mentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of the protective function of ACE‐2 results in downstream dysregulation and imbalance of angiotensin II (Ang II) and angiotensin 1–7 (Samavati & Uhal, 2020). Down‐regulation of ACE‐2 may lead to low vasodilatory levels of angiotensin 1–7 and the unopposed action of Ang II, potentially driving uterine contractions and subsequent preterm birth (Al‐Lami et al, 2021; Dhaundiyal et al, 2021). The unchecked effects of Ang II and subsequent up‐regulation of the renin‐angiotensin system (RAS)/Ang II pathway may also be involved in pre‐eclampsia and have an effect on fetal ACE‐2 reserves.…”
Section: Clinical Manifestations Of Covid‐19 In Pregnant Women and Th...mentioning
confidence: 99%